INDONESIAN MILLENNIALS AND MULTIFORMITY OF UNDERSTANDING OF SUSTAINABLE FASHION NARRATIVE - Rouli Manalu; Nurinda Zahra (Master of Communication Science Program, Universitas Diponegoro, 2023)
This paper examines the ways in which Indonesian millennials build awareness and engage in the global issues of sustainable fashion, which become one of the emerging environment-related issues among Indonesia's younger generations. Some groups of Indonesians millennials take up this issue and begin to campaign for more environmentally-friendly approaches in using fashion, through many different platforms, such as social media, online activities, and offline events. With the increasing popularity of the narrative and the movement, this research is interesting to know the ways in which the young generation of Indonesia understood the narrative and implemented the movement in their own context. This research is particularly interested to see three communities that actively championing this idea in Indonesia; Setali Indonesia, Kekno Klambimu, #TukarBaju movement. In this research, both organizers and participants (followers) of the movements are interviewed to see their understanding, their positions, their motives, and their actions/activisms in engaging in the issues. The result reveals although research participants (or individuals) engaged in this movement and think they were conducting activism under the umbrella of sustainable fashion, their understanding, their application, and their perception about sustainable fashion in relation to broader environmental problems are quite diverse and different from one another. This heterogeneity of understanding and actions generate multiplicity of level of engagement and divergent commitment to the issues. Hence, this paper argues that one particular global issue is possible to be translated to many different forms of actions, as evident among Indonesian millennials' engagement in sustainable fashion.